Ethical Issues and Approaches in Stem Cell Research: From International Insights to a Proposal - Vicini, Andrea (Journal of the Society of Christian Ethics, 2003)
In recent years and months, human stem cell research has dominated many scientists' interests, the media, public debate, and social policy. This paper aims to consider, first, the major scientific data on stem cell research that are available. Second, I reflect on them by examining how they shaped policies in Europe and the United States. I also point to current changes in policy-making concerning the creation of ad hoc committees to address this novel issue and how, in a few instances, different ethical positions are part of the documents produced. In other words, diverse approaches are not solved but kept in tension. Finally, I suggest that the current state of research on human stem cell will benefit from an ethics of risk.